FORMULATION OF SELF-COMPACTING CONCRETE USING RAW MATERIALS OF THE NORTH CAUCASUS - S.-A. Y. Murtazaev; M. Sh. Salamanova; M. S. Hubaev (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Aim. The paper considers the issues associated with the development of formulations of self-compacting concrete.Methods. The basis of the preparation of such concrete is necessary to use effective modern modifiers that improve the rheological properties of the concrete mix and promote enhancement of its physical - mechanical parameters, and fine mineral powders of natural origin. Particular attention is paid to aggregate the results of obtaining graded aggregate obtained by mixing large and small Alagir Chervlensk sand.Results. Cements studied various manufacturers have been allocated the most appropriate of them, it is Portland cement CEM I 42,5N «Chechensemen» and «Novoroscement». Crushed granite was used from diabase rock fractions of 5-20 mm, which was purchased for testing of the RNO-Alaniya. Developed formulations self-compacting concrete, characterized by an intensive set of concrete strength in the early days of its hardening: at the age of 7 days RSZH concrete reaches up to 80% of project strength.Conclusion. The results of the research in this area showed that the raw material potential of North Caucasus Federal District produces selfcompacting concrete class B 25 and B90 and later for monolithic construction, including high-rise.